Analisis Kinerja Keuangan Pemerintahan Daerah Berdasarkan Metode Value For Money Pada Pemerintahan Kota Surakarta Tahun 2020-2022 (Jurnal Kendali Akuntansi, 2024)
The purpose of this research is to measure the financial performance of Surakarta City Local Government using the value for money approach. A qualitative descriptive approach was used in this research. Postpositivist research utilizes natural conditions, with the researcher as the main instrument. Based on the data, the financial performance of the Surakarta City Government was evaluated using economic ratios in 2020-2021, and with an overall average of 85.28%, it fell into the economic category. In terms of efficiency, it is measured by the efficient ratio from 2020-2022 with an overall average of 96.24% but in 2020-2021 which is included in the efficient category and in 2020 it is not included in the efficient category. From the effective side, it is measured by the effective ratio from 2020-2022 with an overall average of 98.74% but only in 2020 which is not included in the effective category and the following year 2021-2022 is included in the effective category.